The effects of serial and acute NaHCO3 loading in well-trained cyclists - Driller, M. W.; Gregory, J. R.; Williams, A. D.; Fell, J. W. (The Journal of Strength and Conditioning Research, 2012)
Many studies have reported substantial performance gains in well-trained athletes after the acute ingestion of sodium bicarbonate (NaHCO3). However, acute NaHCO3 ingestion is not always practical. The aim of this study was to compare acute NaHCO3 loading with serial NaHCO3 loading (split doses over 3 days) in well-trained cyclists. Eight male cyclists (mean ± SD; age = 28 ± 8 years; VO2peak = 66.8 ± 8.4 ml/kg/min) completed 3 tests in a double-blind, randomized design over a 3-week timeframe: acute NaHCO3 loading (AL), serial NaHCO3 loading (SL), and a placebo loading condition (P). After each loading protocol, the cyclists completed a 4-minute performance test on a cycling ergometer. The VO2 was measured during each test, and blood samples were taken throughout the study to measure lactate, bicarbonate ion concentration (HCO-3 ), and pH levels. Both the AL and SL trials produced a significantly higher average power in the 4-minute test (mean ± SD; 3.3 ± 2.0 and 2.3 ± 2.5%; p < 0.001 and p = 0.01, respectively) when compared with the P trial, with no significant difference between AL and SL trials (p = 0.29). The AL trial produced a significantly greater postloading alkalosis as determined by blood HCO-3 when compared with the SL and P trials. Both acute and serial NaHCO3 loading significantly improved 4-minute cycling performance when compared with that in a placebo trial. However, serial NaHCO3 loading may provide a convenient and practical alternative approach for athletes preparing for competition.